2022
DOI: 10.1111/tan.14858
|View full text |Cite
|
Sign up to set email alerts
|

Complement component C3 and C5b‐9 deposition on hypoxia reperfused endothelial cells by non‐HLA antibodies against RhoGDI2: A player involved in graft failure?

Abstract: Antibodies against Rho GDP‐dissociation inhibitor 2 (RhoGDI2) are associated with inferior graft survival in transplant patients receiving a kidney from deceased donors. Although this suggests that these antibodies contribute to graft injury because of ischemia, it remains unknown whether they are also pathogenically involved in the process of graft loss. To study this, we firstly analyzed the IgG subclass profile of anti‐RhoGDI2 antibodies in kidney transplant recipients, and whether antibody titers change ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Though also not a function of RhoGDI2, it was recently reported through a large nationwide cohort study that antibodies against RhoGDI2 can be used as a diagnostic biomarker for long-term kidney graft loss and fibrosis in patients with kidney transplants from deceased donors. Further studies showed that RhoGDI2 autoantibodies were associated with chronic antibody-mediated rejection and inferior graft survival [ 20 , 71 , 72 , 73 , 74 ]. It would be interesting to explore if the autoantibodies against RhoGDI2 can be used as a diagnostic biomarker in other organ transplants.…”
Section: Regulatory Functions Of Rhogdi2mentioning
confidence: 99%
“…Though also not a function of RhoGDI2, it was recently reported through a large nationwide cohort study that antibodies against RhoGDI2 can be used as a diagnostic biomarker for long-term kidney graft loss and fibrosis in patients with kidney transplants from deceased donors. Further studies showed that RhoGDI2 autoantibodies were associated with chronic antibody-mediated rejection and inferior graft survival [ 20 , 71 , 72 , 73 , 74 ]. It would be interesting to explore if the autoantibodies against RhoGDI2 can be used as a diagnostic biomarker in other organ transplants.…”
Section: Regulatory Functions Of Rhogdi2mentioning
confidence: 99%